Виклики для інституційної підтримки відновлення галузевої освіти в Україні в умовах війни (на прикладі лісотехнічної освіти) - Kostiunina, Y. O. (Forestry Education and Science: Current Challenges and Development Prospects, 2024)
Thesis explores the role of local resilience, innovative initiatives, and technological progress in rebuilding Ukraine’s education system in the wake of war. Civil society organizations and educators are creating alternative learning environments and flexible programs adapted to the realities of the conflict. Technology supports coordination between government agencies, optimizing resource allocation and ensuring continuity of learning. Combining local and international efforts helps overcome challenges and shape a sustainable future for Ukrainian education.